Bladder instillation for urinary tract infection prevention in neurogenic bladder patients practicing clean intermittent catheterization: A systematic review. Issue 2 (May 2022) - Ziadeh, Talal; Chebel, Roy; Labaki, Chris; Saliba, Gebrael; Helou, Elie El
Objective: To assess the efficacy and safety of different modalities of bladder instillation in patients with neurogenic bladder practicing intermittent catheterization. Methods: A systematic review of the literature were conducted using two databases: Medline via PubMed and Scopus. Articles evaluating bladder instillation in patients with neurogenic bladder, who are practicing intermittent catheterization, were collected and assessed for the efficacy and safety of the studied agent by two different reviewers. Results: Among the 1896 studies, eight involving 346 patients with neurogenic bladder, were included in this systematic review according to the PRISMA protocols. Gentamicin, Hyaluronic acid, and Lactobacillus rhamnosus was found to decrease the incidence of urinary tract infections, the former reduced multidrug-resistant organisms. Kanamycin-colistin, showed a drop in the mean incidence of bacteriuria in males only. Trisdine, the only studied antiseptic, significantly reduced bacteriuria. Neomycin, however, showed no efficacy in term of bacteriuria. Regarding safety, when evaluated, no major adverse events were reported with any of the studied modalities. Conclusion: Bladder instillations of either antibiotics, antiseptics, hyaluronic acid, or Lactobacillus rhamnosus GG are efficient and safe in patients having neurogenic bladder, with recurrent urinary tract infections and practicing clean intermittent catheterization, with gentamicin being the most recommended product among the different studied agents.